Sediments or soils? Multi-scale geoarchaeological investigations of stratigraphy and early cultivation practices at Kuk Swamp, highlands of Papua New Guinea. (January 2017) - Denham, Tim; Grono, Elle
Abstract: Kuk Swamp is a globally significant archaeological site of early agriculture in the highlands of Papua New Guinea. Mixed-method and multi-scalar investigations of the stratigraphy and selected feature fills at Kuk were instrumental in determining the character of plant exploitation and agricultural practices there during the early and mid Holocene. In this paper, macro-scale (field recording), meso-scale (X-radiography) and micro-scale (thin section micromorphology) analyses are presented in summary form for a stratigraphic column, as well as for a palaeochannel and palaeosurfaces associated with plant exploitation at c.10, 000 cal BP and cultivation at 7000–6400 cal BP. Major and minor stratigraphic units have been characterised, primary and secondary formation processes differentiated, and the anthropic associations of specific stratigraphic units determined, especially in regards to cultivation. The Kuk research highlights several methodological problems with the investigation of early cultivation on allophane-rich soils in tropical environments. Highlights: Multi-scale and mixed method investigation of the stratigraphy at Kuk Swamp. Characterisation of tropical soil formation. Determination of pedogenic attributes associated with cultivation.